The roles of mitochondrial dynamics and NLRP3 inflammasomes in the pathogenesis of retinal light damage. Issue 1 (6th November 2021) - Rong, Rong; Yang, Rongliang; Li, Haibo; You, Mengling; Liang, Zhuotao; Zeng, Zhou; Zhou, Rongrong; Xia, Xiaobo; Ji, Dan
Abstract: With the widespread popularity of electronic products and the diversification of lighting equipment, ocular photochemical damage caused by light has attracted research attention. Although such equipment mainly cause damage to the retina, the specific pathogenesis has not been systematically elucidated. Thus, the goal of this study was to explore the relationship between mitochondrial dysfunction and the activation of the NOD‐like receptor protein 3 (NLRP3) inflammasome in retinal cell death caused by light damage. We used a white light–emitting diode source to establish a mouse model of retinal light damage and observed significant changes of retinal structure and an impairment of visual function. Further experiments revealed that dynamin‐related protein 1 (Drp1)–mediated excessive mitochondrial fission induced overproduction of reactive oxygen species in the retinal cells, leading to apoptosis, activation of microglia, and formation of the NLRP3 inflammasome. This, in turn, triggered a series of inflammatory cascade reactions, leading to pyroptosis. We also carried out red light and Drp1 inhibitor treatment and found that retinal damage and the decline in visual function caused by white light could be partially ameliorated. In conclusion, this study clarified the association between mitochondrial dynamics and the NLRP3 inflammasome in retinal light damage and provides opportunities for therapeutic intervention. Abstract : The goal of this study was to explore the relationship between mitochondrial dysfunction and the activation of the NOD‐like receptor protein 3 (NLRP3) inflammasome in retinal cell death caused by light damage.